Temporalités étagées - Fabien Foureault (Temporalités)
We analyze the structure and dynamics of a particular economic field: LBOs (Leveraged Buy-Outs) in France during the years 2000. Thanks to relational data and written sources from 2000 to 2010, we can try to explain the explosion and implosion of the field by identifying three mechanisms that operate at different and superimposed time scales: financial hegemony, cooperation between competitors, and the reactions to crises. The article illustrates a way of applying social network analysis to formalize an organizational field and to articulate structure and process within meso-level social orders.